Pengaruh Likuiditas Terhadap Dana Pihak Ketiga Pada Bank Umum Syariah Di Indonesia Periode (2019-2021) - Alvin Mohamad Naofal; Eri Puspitasari; Isna Drian Ayu Andani; Agus Eko Sujianto (Universitas 45 Surabaya, 2023)
This research aims to analyze the effect of the equivalent rate, inflation, and liquidity on third-party funds in Islamic banking in Indonesia for the 2019-2021 period. The research population is Islamic banking financial statements with a monthly period from 2019-2021. With the saturated sampling technique, the number of samples is 36 months. The data collection technique used is a documentation study, namely the financial statements of Islamic banking in Indonesia published by the Financial Services Authority and Bank Indonesia. Data processing is done by multiple regression analysis with the help of the SPSS application. Research findings that the equivalent rate affects third party funds, inflation does not affect third party funds and liquidity affects third party funds.